Unintended Lessons of Revolution Student Teachers and Political Radicalism in Twentieth-Century Mexico - Padilla, Tanalis (Duke University Press, 2021)
Tanalís Padilla traces the history of the normales rurales-rural schools in Mexico that trained campesino teachers-and outlines how despite being intended to foster a modern, patriotic citizenry, they became sites of radical politics.